Analysis of Price and Product Perceived Bolster Purchase Decision: Study Case in Fast Food Restaurant in East Bekasi Area - Rahadjeng , Indra Riyana; Handoko, Melyani; Indrarti, Wahyu; Shaura, Rizkiana Karmelia; Rafik, Ahamd; Daniel; Emita, Isyana; Anwar, Dian Mohamad (Journal of Management and Informatics, 2025)
The increasing competition among fast food restaurants in urban areas has made consumers more selective in their purchasing decisions, with price and product quality emerging as key determinants. This study aims to analyze the influence of perceived price and perceived product quality on consumer purchasing decisions at Subway fast food restaurants in East Bekasi. A quantitative approach was applied using a structured questionnaire distributed to 50 consumers. Data were analyzed through multiple linear regression and classical assumption testing. The results indicate that price has a significant and positive effect on purchasing decisions, with a regression coefficient of 1.191 and a partial determination coefficient (R²) of 0.750, suggesting that price alone explains 75% of the decision variance. Similarly, perceived product quality also demonstrates a significant positive effect with a coefficient of 0.469 and R² of 0.724. When combined, both variables explain 72.4% of the variance in purchasing decisions, with the F-test result of 91.673 surpassing the critical value of 3.20. These findings suggest that consumers in East Bekasi prioritize both affordability and quality when choosing fast food. This research contributes to the literature by validating the dual importance of economic and experiential value in fast food marketing strategies, especially in highly competitive suburban environments.